2014
DOI: 10.1186/s12977-014-0089-5
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Vif inhibits G to A hypermutations catalyzed by virus-encapsidated APOBEC3G to maintain HIV-1 infectivity

Abstract: BackgroundHIV-1 viral infectivity factor (Vif) is an essential accessory protein for HIV-1 replication. The predominant function of Vif is to counteract Apolipoprotein B mRNA-editing enzyme-catalytic polypeptide-like 3G (APOBEC3G, A3G), a potent host restriction factor that inhibits HIV-1 replication. Vif mediates the proteasomal degradation of A3G and inhibits A3G translation, thus diminishing the pool of A3G that is available to be packaged into budding virion. Although Vif is robust in degrading A3G, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…As shown in Fig. 6C , HIV-1 Vif markedly degraded huA3G, as reported previously ( 45 , 50 , 51 ), and degraded tsA3Z1a, tsA3Z2a-Z2b, and tsA3Z2d-Z2e to a certain extent but did not degrade tsA3Z2c-Z1b or tsA3Z3. In addition, we found that tsAPOBEC3 proteins could be packaged into HIV-1 particles, the same as huA3G ( Fig.…”
Section: Resultssupporting
confidence: 89%
“…As shown in Fig. 6C , HIV-1 Vif markedly degraded huA3G, as reported previously ( 45 , 50 , 51 ), and degraded tsA3Z1a, tsA3Z2a-Z2b, and tsA3Z2d-Z2e to a certain extent but did not degrade tsA3Z2c-Z1b or tsA3Z3. In addition, we found that tsAPOBEC3 proteins could be packaged into HIV-1 particles, the same as huA3G ( Fig.…”
Section: Resultssupporting
confidence: 89%
“…The primer sets for this study. in the past, new host-virus relations came to be understood by through these molecules (22,23). Previously it has been reported that multiple APOBEC3 enzymes may limit the infectivity of HTLV-1 (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…HIV‐1 counteracts the human restriction factor A3G by expressing the Vif protein, which facilitates the proteasomal degradation of A3G by recruiting an E3 ubiquitin ligase complex, resulting in reduced encapsidation in budding virions 61 . In the results above, we have observed that DNAJB8 mediates autophagic‐lysosomal degradation of HIV‐1 Vif protein.…”
Section: Resultsmentioning
confidence: 55%